2014
DOI: 10.1002/adfm.201400167
|View full text |Cite
|
Sign up to set email alerts
|

Saturated and Multi‐Colored Electroluminescence from Quantum Dots Based Light Emitting Electrochemical Cells

Abstract: Novel light emitting electrochemical cells (LECs) are fabricated using CdSe‐CdS (core‐shell) quantum dots (QDs) of tuned size and emission blended with polyvinylcarbazole (PVK) and the ionic liquid 1‐butyl‐3‐methylimidazolium hexafluorophosphate (BMIM‐PF6). The performances of cells constructed using sequential device layers of indium tin oxide (ITO), poly(3,4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS), the QD/PVK/IL active layer, and Al are evaluated. Only color saturated electroluminescence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 57 publications
0
58
1
Order By: Relevance
“…To circumvent this, for example dyes can be considered. Qian et al [20] recently reported on a quantum dot LEC reaching a similar luminescent efficiency as a multilayer quantum dot OLED, despite the presence of some efficiency roll off. Further optimization of such systems may lead to efficient, single layered electroluminescent devices, combining the high efficiencies of OLEDs and the easy processing of LECs.…”
mentioning
confidence: 99%
“…To circumvent this, for example dyes can be considered. Qian et al [20] recently reported on a quantum dot LEC reaching a similar luminescent efficiency as a multilayer quantum dot OLED, despite the presence of some efficiency roll off. Further optimization of such systems may lead to efficient, single layered electroluminescent devices, combining the high efficiencies of OLEDs and the easy processing of LECs.…”
mentioning
confidence: 99%
“…[8][9][10] Thus, to define clear guidelines to design LEC materials that are intrinsically able to decouple charge transport and emission is a challenge in the field. [8][9][10] As an alternative, the host-guest approach by (i) using OLED-host materials doped with ionic liquids, 11 (ii) mixtures of iTMCs, [12][13][14] and (iii) using ionic-based small-molecule charge transporters, 15 has been explored in LECs to date. All these approaches show the typical problem of the host-guest strategy, that is, to determine the optimum doping level and effective doping range, which are typically very low and narrow, respectively.…”
mentioning
confidence: 99%
“…Leger and co-workers reported on an LEC device based on a binary blend of CdSe/ZnS core-shell quantum dots (QDs) as the emitter [18], and in a later study red, green, blue and broadband-white emission at an efficiency of CE *1 cd/A was delivered from a ternary-QD LEC though a careful control of the composition of the active material and the applied voltage [19]. A current promising material group in the field of organic photovoltaics [132] and optoelectronics [133,134] is the perovskites, and Costa and co-workers recently demonstrated a functional spraydeposited perovskite LEC [20].…”
Section: Performance: Achieving Fast Turn-on High Efficiency and Lomentioning
confidence: 99%
“…It should, however, be acknowledged that a vast majority of the subsequent research on iTMC-LECs have employed an additional electrolyte (often an ionic liquid) in order to attain a reasonably fast turn-on time [4,5]. The LEC field has up until now been dominated by these two principal classes of compounds, although new groups of functional materials, in the form of non-ionic luminescent small molecules [6][7][8][9][10][11][12][13][14], ionic fluorescent small molecules [15][16][17], quantum dots [18,19], and perovskites [20,21], have emerged more recently. Figure 1c presents the chemical structures of a CP, an iTMC, and a luminescent small molecule, as well as a number of electrolytes that have been utilized in recent high-performance LEC devices.…”
Section: Introductionmentioning
confidence: 99%